Development of Learning Videos Assisted by Instagram Media on the Reaction Rate Content - Tri Patmawati Adriana; Eny Enawati; Eni Mayasari (QUANTUM: Jurnal Inovasi Pendidikan Sains, 2025)
Chemistry is the study of matter and the changes that accompany it. Chemical matter is defined as everything that has mass and occupies space. Chemical materials can be single substances (elements) or mixed substances (compounds). Based on the results of an interview with a teacher at SMAN 7, Pontianak revealed that students have difficulty in learning the reaction rate especially in understanding the reaction rate concept, where students can only repeat the definition of the reaction rate without understanding the real meaning so that they tend to rely on memorization alone. The abstract nature of reaction rate content is also one of the reasons why students have difficulty in learning reaction rate content.  The purpose of this study was to develop Instagram media-based learning videos on reaction rate content and to determine the level of validity and students' responses to these learning videos to increase efficient and effective knowledge. This research uses the Research and Development (R&D) approach of the ADDIE model (Analyze, Design, Develop, Implement, Evaluate), with only the Analyze, Design, and Develop stages applied. Data collection techniques used, namely direct communication techniques interviews and indirect communication in the form of validity test questionnaire sheets and wide stundent response test questionnaires, with research instruments in the form of feasibility assessment sheets and student response questionnaires. The results proved that the average percentage of content validity was 95.9%, and media validity was 98%, both with very valid criteria. The average percentage of student responses in the small group test reached 83.3% with very good criteria, while in the large group test it was 91.25%. In addition, the average percentage of teacher responses reached 88%, with very good criteria, thus it can be concluded that the learning video assisted by Instagram media on reaction rate material is declared very feasible to use.